1993
DOI: 10.1002/1097-4679(199311)49:6<799::aid-jclp2270490607>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Sense of humor and dimensions of personality

Abstract: Previous researchers have demonstrated relationships between sense of humor and personality. Most have viewed sense of humor from the perspective of humor appreciation. Others have taken the approach that sense of humor has two factors: appreciation and creativity. Our approach has been to look at sense of humor as made up of creativity and several additional elements. The present study reports on the factor analysis of a Multidimensional Sense of Humor Scale, as well as correlates of various elements of sense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0
4

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 18 publications
4
52
0
4
Order By: Relevance
“…The relationship of humor production to extraversion is also consistent with previous research (Köhler and Ruch, 1992;Thorson and Powell, 1993b). The current study showed that extraversion corresponds to facets of sociability (e.g., "have a lot to say", "feel comfortable around people"), dominance (e.g., "like to draw attention to myself"), and active sensation seeking (e.g., "am the life of the party").…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship of humor production to extraversion is also consistent with previous research (Köhler and Ruch, 1992;Thorson and Powell, 1993b). The current study showed that extraversion corresponds to facets of sociability (e.g., "have a lot to say", "feel comfortable around people"), dominance (e.g., "like to draw attention to myself"), and active sensation seeking (e.g., "am the life of the party").…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with previous studies on sex differences in humor (Thorson and Powell, 1993b;Ziv, 1984) as well as Miller's sexual selection model that reproductive benefits for humorous displays would be greater for males than females (Miller, 2000c). Table 4 displays the bivariate correlations showing sex differences with regard to humor production.…”
Section: Sex Differences In Humor Productionmentioning
confidence: 99%
“…The reliability values were similar to the original version (α = 0.92), [12] US samples (α = 0.91), [13,14] Croatia (α = 0.88), [14] Australia (α = 0.92), [16] Spain (α = 0.89), [17] Portugal (α ranged from 0.63 to 0.93), [6,18] China (α = 0.88) [19] and Mexico (α = 0.91). [20] The α values obtained in this study are considered good.…”
Section: Reproducibilitymentioning
confidence: 99%
“…The results differ from the original version that had four factors, [12] as well as, versions in US samples, [13] China [19] and Mexico. [20] Nevertheless, in a US [14] study performed on young and old people, six factors were found concerning the elderly sample.…”
Section: Validitymentioning
confidence: 99%
See 1 more Smart Citation